Extra-buccal surgical access for canine removal included in mandibular symphysis: case report - Lucas Augusto Pereira SOUTO; Daniela MENESES-SANTOS; Cristovão Marcondes de Castro RODRIGUES; Claúdia Jordão SILVA; Flaviana Soares ROCHA; Marcelo Caetano Parreira da SILVA (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT Included teeth are all the dental elements that arrive the normal time of its eruption, remains immersed within the tissues. Usually found when missing a tooth, or on routine radiographic examinations. In the presence of included teeth, it is necessary to define the best treatment approach, whether it is surgical, through exodontia, or by orthodontic tracings. Inclusive canines, in the symphysis region and near the base of the mandible, are rare and make the use of orthodontic traction techniques contraindicated. Presence of teeth in the intraosseous ectopic position can cause injuries, such as alveolodentary ankylosis, calcium metamorphosis of the pulp and aseptic pulp necrosis, among others. Anamnesis, physical examination (intra- and extraoral) and radiographic examinations such as panoramic, periapical, computed tomography, and occlusal radiographs should be performed to make the diagnosis adequate. In general, the success of the treatment depends on the age of the patient and the position of the canines at the time of the surgical procedure. The objective of this work is the extraction of a lower canine with extra-oral access in an outpatient clinical setting under local anesthesia.